Mechanism Involved in Acute Liver Injury Induced by Intestinal Ischemia-Reperfusion - Jin, Binghui; Li, Guangyao; Zhou, Lin; Fan, Zhe (Frontiers in Pharmacology, 2022)
Intestinal ischemia-reperfusion (I/R) is a common pathophysiological process, which can occur in many conditions such as acute enteric ischemia, severe burns, small intestinal transplantation, etc. Ischemia-reperfusion of the intestine is often accompanied by distal organ injury, especially liver injury. This paper outlined the signal pathways and cytokines involved in acute liver injury induced by intestinal I/R: the NF-κB Signaling Pathway, the P66shc Signaling Pathway, the HMGB1 Signaling Pathway, the Nrf2-ARE Signaling Pathway, the AMPK-SIRT-1 Signaling Pathway and other cytokines, providing new ideas for the prevention and treatment of liver injury caused by reperfusion after intestinal I/R.